(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Successful functioning of any enterprise is implemented due to effective organization of work of collective. Effectivemanagementisdeterminedby correct orientation and interested activity of collective stuff. Strictdirectiveprogramsarenotencouragedinenterprise, on the contrary, initiative, relative autonomy, free choice of entrepreneur is necessary for successive work. Creative approach is recommended. In the article it is analyzed the valuable problems of formation of Kazakhstan entrepreneurship. Key words: culture of the enterprise, mass culture, pragmatism, subculture, values, firm, elite culture.